Csendország - Lakatos, Róbert (Hungary : Inforg Stúdió, 2001)
The young deaf-mute boy who lives in a small village in Gyimes (Transylvania) receives a camera from his parents. What does the experience of "light-writing" mean to a hearing-impaired child? What traces does the rediscovery of the usual material and natural environment, capturing experiences, leave on the development of Alfi's personality? What perspectives does this new form of communication open for a disabled boy? Róbert Lakatos's attitude is empathic and sensitive enough to help us to find answers to these questions, using his film as a mirror. Although the filmmaker never actually appears in the film, the friendship between him and his protagonist gives the basic tone of the film.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films